Book Reviews. (1st October 2013) - Baker, Charlotte; Bromilow, Pollie; Frith, Nicki; Kosniowski, Jenny; Majumdar, Margaret A.; McIlvanney, Siobhán; Tarica, Estelle; Thomas, Bonnie; Yaacoub, Faten; Zayzafoon, Lamia
La Création Romanesque chez Williams Sassine, Philip Amangoua Atcha (2011) Paris: Harmattan, 252 pp., ISBN: 978-2-296-55053-7, p/bk, 23.50A Taste for the Foreign: Worldly Knowledge and Literary Pleasure in Early Modern French Fiction, Ellen R. Welch (2011) Newark: University of Delaware Press, xxviii + 225pp., ISBN: 978-1-61149-062-6, h/bk, £44.95Violence in Francophone African & Caribbean Women's Literature, Chantal Kalisa (2009) Lincoln, NE: University of Nebraska Press, 225 pp., ISBN: 978-0-8032-1102-5, h/bk, $45.00Writing Postcolonial France: Haunting, Literature, and the Maghreb, Fiona Barclay (2011) Plymouth: Lexington Books, 152 pp, ISBN: 978-0-7391-4503-6, h/bk, $64.99, £39.95La Terre et le sang/Land and Blood (trans. Patricia Geesey), Mouloud Feraoun ([1953]) 2012) Charlottesville/London: University of Virginia Press, 243 pp., ISBN: 978-0-8139-3220-0, h/bk, $59.50; ISBN: 978-0-8139-3221-7, p/bk, $22.50Cherchez la femme: Women and Values in the Francophone World, Erika Fülöp and Adrienne Angelo (eds) (2011) Newcastle upon Tyne: Cambridge Scholars Publishing, 292 pp., ISBN: 978-1-4438-2933-5, h/bk, £39.99Patrick Chamoiseau: A Critical Introduction, Wendy Knepper (2012) Jackson: University Press of Mississippi, 274pp., ISBN: 978-1-61703-154-0, h/bk, ebook 978-1-61703-155-7, $55Beyond the Slave Narrative: Politics, Sex, and Manuscripts in the Haitian Revolution, Deborah Jenson (2011) Liverpool: Liverpool University Press, 322 pp., ISBN: 978-1-84631-497-1, h/bk, £65, ISBN: 978-1-84631-760-6, p/bk, £16.99Postcolonial Poetics: Genre and Form, P. Crowley and J. Hiddleston (2011) Liverpool: Liverpool University Press, 279 pp., ISBN: 978-1-84631-745-3, h/bk £55.85Francophone Women: Between Visibility and Invisibility, Cybelle H. McFadden and Sandrine F. Teixidor (eds) (2010) New York: Peter Lang, Francophone Cultures and Literatures, 143 pp., ISBN: 978-1-4331-0803-7, h/bk, 60, £48